Alkaloids from Veratrum taliense Exert Cardiovascular Toxic Effects via Cardiac Sodium Channel Subtype 1.5 - Gan Wang; Ming-Qiang Rong; Qiong Li; Ya-Ping Liu; Cheng-Bo Long; Ping Meng; Hui-Ming Yao; Ren Lai; Xiao-Dong Luo (Toxins, 2015)
Several species of the genus Veratrum that produce steroid alkaloids are commonly used to treat pain and hypertension in China and Europe. However, Veratrum alkaloids (VAs) induce serious cardiovascular toxicity. In China, Veratrum treatment often leads to many side effects and even causes the death of patients, but the pathophysiological mechanisms under these adverse effects are not clear. Here, two solanidine-type VAs (isorubijervine and rubijervine) isolated from Veratrum taliense exhibited strong cardiovascular toxicity. A pathophysiological study indicated that these VAs blocked sodium channels NaV1.3–1.5 and exhibited the strongest ability to inhibit NaV1.5, which is specifically expressed in cardiac tissue and plays an essential role in cardiac physiological function. This result reveals that VAs exert their cardiovascular toxicity via the NaV1.5 channel. The effects of VAs on NaV1.3 and NaV1.4 may be related to their analgesic effect and skeletal muscle toxicity, respectively.